Reliability Improvement by Adopting Ti-barrier Metal B for Porous Low-k IL Structure - Sakata, A.; Yamada, M.; Hasunuma, M.; Takahashi, S.; Yamada, A.; Hasegawa, T.; Kaneko, H.; Yamashita, S.; Omoto, S.; Hatano, M.; Wada, J.; Higashi, K.; et al. (Proceedings of the IEEE International Interconnect Technology Conference, 2006)
This paper elucidated for the first time that titanium (Ti) is an excellent barrier metal (BM) material from the stand point of cost and performance, especially for the porous low-k ILD materials. Both stress induced voiding (SIV) suppression and one order longer electromigration (EM) lifetime were obtained by introducing Ti instead of the conventional tantalum (Ta). It has been considered that the smaller volume change when oxidized and the existence of metallic Ti-O solid-solution phase for Ti would be the reason for its control of moisture penetration from the low-k ILD materials which resulted in excellent SIV suppression. No electrical resistance increase due to intermetallic reaction between Cu and Ti was observed. Furthermore, the suppression of Cu grain boundary migration was attributed to the segregation of Ti atoms at the Cu grain boundaries. This resulted in higher interconnect reliability